GCS Interface Mission Load Reduction Design through Pilot Gaze Point Analysis - Lee, Sedam; Kwon, Yongjin; Heo, Jinyeong; Kim, Jooyoung (International Journal of Mechanical Engineering and Robotics Research, 2022)
Due to recent technological advancement, the interest in the commercialization of unmanned aerial vehicles(UAVs) is increasing rapidly. UAVs are continuously being studied for various applications and purposes. As the purpose and use of UAVs expand, the demand for the pilot ability for safe and successful flight is also increasing. Due to the nature of the UAVs, it takes a long time for the pilots to become proficient. Despite, if a difficult situation arises during a flight and the pilot’s workload unexpectedly rises, an accident may occur. This is mainly due to mission load hike and inexperienced operation. Therefore, there is a need for a new GCS interface design to reduce the mission load, while increasing the mission success rate. In this paper, we propose a new method to design a more efficient GCS interface, and the new design has bene verified for its efficiency. The pilot gaze was tracked during mission operation using the newly designed GCS interface. The interface components were analyzed through the tracked gaze, and a GCS interface was evaluated. As a result of deriving the arrangement method with the shortest gaze path, the new GCS interface is found to be an efficient arrangement. At the same time, the new interface design shares the same ergonomic design principles, which proves to be fulfilling the design purposes.
Keywords: Fatigue reduction; Gcs interface; Mission load; Operation efficiency; Pilot gave; Uav flight